ANALYSIS OF THE SUSTAINABILITY OF WARSHIP OPERATIONS IN SECOND FLEET COMMAND FOR SUPPORTING THE TASKS OF THE INDONESIAN NAVY - Tri Sumarsono; Sutrisno Sutrisno; Azi Wardiana (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
Indonesian Warships are a representation of the strength and ability of the Navy in maintaining state sovereigntyin the area of national jurisdiction. Second Fleet Command is one of the main cities of the Indonesian navy whichoversees the central part of the Republic of Indonesia. This maritime area security activity is realized through theimplementation of Marine Defense Operations and Marine Security Operations using the warship. In assessingaspects, criteria and alternatives that affect the sustainability of the warship operation degree in Second FleetCommand, the author uses the Analytical Hierarchy Process method (AHP) in assessing the weight of eachintensity, in this processing the author uses super decision software 2.10 in processing the data. In theimplementation of warship operations, there are many aspects that affect its implementation. The three mainaspects are the Geopolhankam aspect, the naval warships technical/physical aspect and the Navy'sfinancial/budgetary aspect. Of the three aspects, the technical aspect is the main aspect that affects thesustainability of the warships operation title with a weight value of 0.44343. Furthermore, the Financial aspect /Indonesian navy budget with a weight of 0.38737 and the Geopolhankam aspect is the aspect with the lowestpriority with a weight of 0.1692. In the threat level criteria, regional conflicts have the highest value with a weightvalue of 0.16398, in the Indonesian Navy budget criteria the budget for carrying out the tasks of the Navy is thehighest criterion with a weight value of 0.19437,Keywords: warship operation, Operation Pattern, Analytical Hierarchy Process (AHP), Super Decision 2.10